UMP students use Adab UMP cash coupon app Food Campus - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 29 December 2021 - In line with the university’s aspiration towards a digital campus, Universiti Malaysia Pahang (UMP) students will adapt the UMP Kasih facility, namely Meal Coupons for students who are in need, using the Adab@UMP app to enable eligible students to get free food from the campus cafeteria.